2006
DOI: 10.1089/ten.2006.12.ft-185
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on the Bone Healing around Calcium Phosphate?Coated and Non-coated Oral Implants in Trabecular Bone

Abstract: The effect of local application of autologous platelet-rich plasma (PRP) on bone healing in combination with the use of titanium implants with 2 different surface configurations was investigated. PRP fractions were obtained from venous blood sample of 6 goats and applied via gel preparation and subsequent installation in the implant site or via dipping of the implant in PRP liquid before insertion. Thirty-six implants (18 non-coated and 18 calcium phosphate (CaP) coated) were placed into the goat femoral condy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 21 publications
4
27
0
1
Order By: Relevance
“…28,46,47 Furthermore, a layer of liquid-PRP sprayed onto the implant surface before insertion showed a tendency to increase the bone apposition to roughened titanium implants during early healing phase. 48,49 All of these findings may therefore support the clinical use of PRP during oral bone regenerative procedures where differentiation and proliferation of bone cells at the site of surgery is required.…”
Section: Tablementioning
confidence: 75%
“…28,46,47 Furthermore, a layer of liquid-PRP sprayed onto the implant surface before insertion showed a tendency to increase the bone apposition to roughened titanium implants during early healing phase. 48,49 All of these findings may therefore support the clinical use of PRP during oral bone regenerative procedures where differentiation and proliferation of bone cells at the site of surgery is required.…”
Section: Tablementioning
confidence: 75%
“…A clinical study in which 1391 implants were placed in 295 patients after bioactivating the surface with PRGF, stability and implant survival were evaluated, and it was reported that 99.6% of the implants treated with PRGF were well osseointegrated suggesting that the clinical use of this technique in oral implantology can improve the prognosis (Anitua, 2006). Animal studies in which platelet-rich plasma in liquid form was applied to the implant surface by dipping the implant in PRP prior to placement have demonstrated that PRP in a liquid form showed a tendency to increase bone apposition to roughened titanium implants (Nikolidakis et al, 2008, Nikolidakis et al, 2006. Nikolidakis et al (2006) investigated the effect of local application of autologous platelet-rich plasma (PRP) on bone healing in combination with the use of titanium implants with 2 different surface configurations -CaP coated and non-coated implants.…”
Section: Future Directions In Implant Surface Modificationsmentioning
confidence: 99%
“…Animal studies in which platelet-rich plasma in liquid form was applied to the implant surface by dipping the implant in PRP prior to placement have demonstrated that PRP in a liquid form showed a tendency to increase bone apposition to roughened titanium implants (Nikolidakis et al, 2008, Nikolidakis et al, 2006. Nikolidakis et al (2006) investigated the effect of local application of autologous platelet-rich plasma (PRP) on bone healing in combination with the use of titanium implants with 2 different surface configurations -CaP coated and non-coated implants. PRP fractions were obtained from venous blood sample of 6 goats and applied via gel preparation and subsequent installation in the implant site or via dipping of the implant in PRP liquid before insertion.…”
Section: Future Directions In Implant Surface Modificationsmentioning
confidence: 99%
“…PRP was harvested from blood for tissue regeneration because of the many factors within it that activate osteoid production, collagen synthesis and cell proliferation (Frechette et al, 2005;Uggeri et al, 2007). In addition, the fibrinogen in PRP gel gives it a fibril structure that, when mixed with thombin or calcium chloride, creates a plastic substance that easily moulds to fit a defect (Nikolidakis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%